The Role Of User Satisfaction In Influencing The Quality Of Information And Shopee Chatbot Services On Continuation Intention - Ulil Albab; Agus Supriyanto (Journal of Business and Management Inaba, 2026)
This study aims to analyze the effect of information quality and service quality of the Shopee chatbot on users' continuance intention with user satisfaction as a mediating variable. This research employed a quantitative approach using primary data collected through questionnaires distributed to 160 Shopee users in Kudus Regency who had used the Shopee chatbot service. The sampling technique used purposive sampling, while data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS software. The results showed that information quality and service quality have a positive and significant effect on continuance intention. In addition, user satisfaction also has a positive and significant effect on continuance intention. Information quality and service quality were proven to significantly influence user satisfaction. Furthermore, user satisfaction was able to mediate the relationship between information quality and service quality on continuance intention. These findings indicate that accurate information, responsive service, and user satisfaction are important factors in increasing users' intention to continuously use the Shopee chatbot service. Therefore, improving chatbot performance through better information quality and service quality can strengthen user loyalty toward digital services.